Multiplex PCR-based identification of Streptococcus canis, Streptococcus zooepidemicus and Streptococcus dysgalactiae subspecies from dogs. (February 2017) - Moriconi, M.; Acke, E.; Petrelli, D.; Preziuso, S.
Highlights: The multiplex-PCR identifies some canine streptococci that are considered or suspected as emerging zoonotic bacteria. The PCR demonstrates high sensitivity and specificity when bacterial isolates or clinical specimens from dogs are tested. The multiplex-PCR is time- and reagent-saving in comparison with other identification methods. The multiplex-PCR can be useful for diagnosis or epidemiological purposes or when bacterial culture is not possible. Abstract: Streptococcus canis ( S. canis ), Streptococcus equi subspecies zooepidemicus ( S. zooepidemicus ) and Streptococcus dysgalactiae subspecies ( S. dysgalactiae subspecies) are β-haemolytic Gram positive bacteria infecting animals and humans. S. canis and S. zooepidemicus are considered as two of the major zoonotic species of Streptococcus, while more research is needed on S. dysgalactiae subspecies bacteria. In this work, a multiplex-PCR protocol was tested on strains and clinical samples to detect S. canis, S. dysgalactiae subspecies and S. equi subspecies bacteria in dogs. All strains were correctly identified as S. canis, S. equi subspecies or S. dysgalactiae subspecies by the multiplex-PCR. The main Streptococcus species isolated from symptomatic dogs were confirmed S. canis . The multiplex-PCR protocol described is a rapid, accurate and efficient method for identifying S. canis, S. equi subspecies and S. dysgalactiae subspecies in dogs and could be used for diagnostic purposes and for epidemiological studies.